2011
DOI: 10.1002/sce.20483
|View full text |Cite
|
Sign up to set email alerts
|

Young African American children constructing academic and disciplinary identities in an urban science classroom

Abstract: In this paper, I offer a framework for exploring the academic and disciplinary identities young African American children construct in urban science classrooms. Using interviews, fieldnotes, and videotapes of classroom lessons, I juxtapose the ways in which two children tell about their experiences in school and science with their performances of self in the midst of complex, spontaneous classroom engagements with their peers and teacher. I found that the children's performances of self in the classroom were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 55 publications
1
59
0
1
Order By: Relevance
“…When we situate our work within the science identity context, it is conceptualized as an “affinity identity” or the conception that “we are what we are because of the experiences we have had within certain sorts of affinity groups” (p. 101). Other work in science education has framed science identity as a “disciplinary identity” or as a person's understandings of self in relation to a discipline (Kane, ). Our framing of STEM identity is similar to other work in science education in which disciplinary identity is interactive with many other identities a person may ascribe to and is multidimensional in its construction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When we situate our work within the science identity context, it is conceptualized as an “affinity identity” or the conception that “we are what we are because of the experiences we have had within certain sorts of affinity groups” (p. 101). Other work in science education has framed science identity as a “disciplinary identity” or as a person's understandings of self in relation to a discipline (Kane, ). Our framing of STEM identity is similar to other work in science education in which disciplinary identity is interactive with many other identities a person may ascribe to and is multidimensional in its construction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, as Kane [2009Kane [ , 2012a has argued, in order to understand student IC in classrooms, attention is needed to student identities not only in narrated contexts (the stories, or narratives, they develop about who they are and how they are positioned) but also in performed contexts (the identities-in-practice that they perform in the classroom). Considering the three types of identities that are important in the CLIC framework, we offer three sets of questions as analytical tools for thinking about, and for understanding, construction of identities performed in the science and mathematics classroom ( table 2 ).…”
Section: Recommendations For Practice and Researchmentioning
confidence: 99%
“…In another study, analyzing both the ways a class of Black third graders spoke about or narrated their experiences of school and science and the ways they performed themselves in the moment-to-moment happenings of the science class throughout one whole school year, Kane [2009Kane [ , 2012a found that children constructed a consistent sense of who they believed themselves to be as students and science students and scientists and how they acted in the science class, albeit differently from each other (another example related to section 10 of fig. 3 ).…”
Section: Academic Identity and Its Influence On Disciplinary Identitymentioning
confidence: 99%
See 1 more Smart Citation
“…We also situate this study amidst identity studies literature with our focus on individuals' agency and multi‐level structures that enable and constrain agency (Archer et al, 2012; Elmesky, ; Jackson & Seiler, ; Kane, ; Seiler, ; Tan, Calabrese Barton, Kang, & O'Neill, ; Wood, Erichson, & Anicha, ). If students claim to dislike science in middle school after loving it in elementary school, we must probe more deeply into the cultural (implicit) meanings of science in their school science experiences.…”
mentioning
confidence: 99%